SISTEM PENGELOLAAN LIMBAH MEDIS PADAT DAN CAIR SERTA FAKTOR-FAKTOR YANG BERKAITAN DENGAN PELAKSANAAN PENGELOLAAN LIMBAH MEDIS PADAT DAN CAIR DI RUMAH SAKIT UMUM KABANJAHE KABUPATEN KARO TAHUN 2015 - putri yani; nurmaini *; surya dharma (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTIn providing the health service for the community, hospital result solid and liquid waste that can harm the health and environment if it is not handle properly. That’s why we need to analyze the process of solid and liquid medical waste management and the factors that support the implementation ofsolid and liquid medical waste management in hospital.The type of this research is descriptive survey that analyze the system of solid and liquid medical waste management as and to determine the factors that affect the implementation of solid and liquid medical waste management in Rumah Sakit Umum Kabanjahe on 2015. The object of this research is the management unit of solid and liquid medical waste. The data were obtained by interview and observation based on Kepmenkes RI No. 1204 on 2004 and analyzed descriptively.The result showed that the management of solid and liquid medical waste is still not in accordance. In management of solid medical waste, the stage of sorting between medical and non medical waste, collection use the whellbarow open, destruction in incenarator and final disposal are not yet qualified. The personel of waste processing is still not untrained because the hospital never gave training, facilities and infrastructure are still noteligible also. In management of liquid medical waste, the process of management are still not optimal, and there is not any inspection process for the effluent quality of liquid medical waste.The conclusion of this research is the medical management of solid and liquid waste in RSU Kabanjahe are not eligble. The tool of receiving station are not equipped with solid medical waste plastic bags and the colour of container is not appropriate with the kind of waste. Means of transport used is the whellbarow open. The liquid medical waste treated in the IPAL with stream flow filter system with it’s working principle is based on active sludge but not examined the quality of effluent before being discharged into the environment. Facilities and infrastructure are still not fulfill the criteria so it need more repairing, and the implementation of the guidelines which accordance with the goverment regulations.Key word : management of medical waste, solid, liquid and hospital